2014
DOI: 10.1007/jhep08(2014)021
|View full text |Cite
|
Sign up to set email alerts
|

2d gauge theories and generalized geometry

Abstract: We show that in the context of two-dimensional sigma models minimal coupling of an ordinary rigid symmetry Lie algebra g leads naturally to the appearance of the "generalized tangent bundle" TM ≡ T M ⊕ T * M by means of composite fields. Gauge transformations of the composite fields follow the Courant bracket, closing upon the choice of a Dirac structure D ⊂ TM (or, more generally, the choide of a "small Dirac-Rinehart sheaf" D), in which the fields as well as the symmetry parameters are to take values. In the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…Such systems have been under investigation for their relation to the yet elusive dynamics of multiple M5 branes, see e.g., [20][21][22][23][24][25][26]. A similar analysis of the general tensor hierarchy developed in [7] will be presented in a forthcoming paper [27].…”
Section: Introductionmentioning
confidence: 97%
“…Such systems have been under investigation for their relation to the yet elusive dynamics of multiple M5 branes, see e.g., [20][21][22][23][24][25][26]. A similar analysis of the general tensor hierarchy developed in [7] will be presented in a forthcoming paper [27].…”
Section: Introductionmentioning
confidence: 97%
“…Thus it is natural to wonder whether one can construct gauge field theories without having at hand a group action, working directly at the level of foliations. Such a task was undertaken in our recent work [1,2], building on [3][4][5]. In this contribution we review and clarify the main ideas and some of the results found there, namely on the gauging of a singular foliation in the case of 2D bosonic σ -models.…”
Section: Introduction and Motivationsmentioning
confidence: 90%
“…Such an action was first studied in [35] and more recently in [5,37,38]. As in the minimally coupled case, we examine the gauge invariance of S W Z under the transformations δ ε X i and δ ε A a .…”
Section: On the Construction Of Gauge Theories: The Traditional And Tmentioning
confidence: 99%
“…[16][17][18][19][20]. The essence of this formulation relies on an extension of the standard infinitesimal gauge transformations for the gauge fields A a to include a part proportional to DX i , where X i are the world sheet scalars and DX i is the gauge covariant derivative on the world sheet obtained by minimal coupling.…”
Section: Jhep01(2016)154mentioning
confidence: 99%
“…Recall that the 2-form that multiplies the Lagrange multipliers in Buscher's procedure is precisely the field strength of the corresponding gauge fields. In the present formulation this turns out to be 19) which is the same as the one considered in ref. [20].…”
Section: Jhep01(2016)154mentioning
confidence: 99%